Novel FOXF1 Mutations in Sporadic and Familial Cases of Alveolar Capillary Dysplasia with Misaligned Pulmonary Veins Imply a Role for its DNA Binding Domain. Issue 6 (12th April 2013) - Sen, Partha; Yang, Yaping; Navarro, Colby; Silva, Iris; Szafranski, Przemyslaw; Kolodziejska, Katarzyna E.; Dharmadhikari, Avinash V.; Mostafa, Hasnaa; Kozakewich, Harry; Kearney, Debra; Cahill, John B.; Whitt, Merrissa; et al.
<x xml:space="preserve">Abstract</x> FOXF1 mutations result in Alveolar Capillary Dysplasia with Misaligned Pulmonary Veins, a deadly neonatal lung disorder that is uniformly fatal. The data in the article is the outcome of a global collaboration presenting the up to date list of causative mutations in FOXF1. The maternally inherited familial cases support the paternal imprinting of the gene in human lungs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>